The Cytological Spectrum of Major Salivary Gland Lesions: An Observational Study - Devi, R Bhuvanamha; Shivashekar, G; Ganapathy, Hemalatha; ., Aruna; ., Geetha (Annals of Pathology and Laboratory Medicine, 2018)
Background: Fine needle aspiration cytology (FNAC) is an accurate, cost effective & safe technique for diagnosing salivary gland lesions. We conducted this study to observe the cytological spectrum of different salivary gland lesions in tertiary care hospitals. Methods: This is a prospective study carried from June 2010 to April 2014 at SBMCH Chromepet and SRM MCH & RC, Potheri. Fine needle aspiration was performed on patients presenting with complaints of salivary gland lesions. Data was statistically analyzed. Result: FNAC is performed on total of 135 salivary gland lesions. 11 were non diagnostic aspirate (8.2%), 58 were non neoplastic lesions (42.9%) and 66 were neoplastic lesions (48.9%). The most common benign tumor of salivary gland is pleomorphic adenoma and mucoepidemoid carcinoma was the most common malignant tumor. The most common major salivary gland involved is parotid gland. Conclusion: In the present study, neoplastic lesions were more common than non-neoplastic lesions. We conclude that inspite of few diagnostic pitfalls FNAC still plays a vital role in differentiating neoplastic from non- neoplastic salivary gland lesions to provide guideline for appropriate patient management. KEYWORDS: Cytology, FNAC, Salivary Gland, Neoplastic Lesion, Non-Neoplastic Lesion.